91: The Canadian Neonatal Follow-Up Network. Issue 6 (1st June 2014) - Synnes, A; Luu, T; Moddemann, D; Church, P; Lee, D; Vincer, M; Ballantyne, M; Majnemer, A; Creighton, D; McGuire, M; Sauve, R; ,
Abstract: BACKGROUND: The Canadian Neonatal Follow-Up Network (CNFUN), a collaboration between all 26 Neonatal and Perinatal Follow-up Programs in Canada, was developed in liaison with the Canadian Neonatal Network (CNN) to facilitate collaboration in research, integrated data collection, knowledge translation and to improve the quality of care and long term outcomes of children seen in their programs. CNFUN implemented a standardized assessment at 18 months corrected age (CA) and a three year CA questionnaire for all survivors <29 weeks gestational age starting with births April 1, 2009 onwards. OBJECTIVES: Describe the cohort of CNFUN preterm subjects born April 1, 2009 to July 1, 2011 and major adverse outcomes. DESIGN/METHODS: NICUs notified local follow-up programs of eligible subjects. Patients were evaluated according to a standardized protocol and data manual. Bayley -III assessors completed online training specific for this study. Deidentified data was uploaded. Data was extracted from the CNFUN database to calculate cerebral palsy, hearing and visual impairment rates and outcomes on the Bayley -III cognitive, motor and language scores. Linkage with the Canadian Neonatal Network is planned. RESULTS: Of 2528 infants, 2109 were seen at 18 months CA. Subjects with missing information: CP status 45, Bayley III-cognitive 151, Bayley III language 210, Bayley III motor 222, hearing 139 and vision 59. CONCLUSIONS: Neurodevelopmental outcomes confirm a relatively low incidence of severe adverse outcomes but a significant percentage with scores <85 on the Bayley-III. This large CNFUN cohort of preterm survivors is a promising source of data for further analyses.